Valorisation of Raspberry Seeds in Cosmetic Industry-Green Solutions - Ivanka Ćirić; Dragana Dabić Zagorac; Milica Sredojević; Milica Fotirić Akšić; Biljana Rabrenović; Stevan Blagojević; Maja Natić (MDPI AG, 2024)
The fruit processing industry generates large quantities of by-products well known to be rich in bioactive compounds with numerous nutritional properties and beneficial effects for human health. We developed a strategy to valorise raspberry seeds and obtain valuable ingredients with potential application in cosmetic skincare formulas. Cold press extraction technology was applied to extract oil, and the remaining defatted raspberry seed cake was treated with three proline based deep eutectic solvents (DES) to extract polyphenols. The most potent was proline/citric acid extract, with free and total ellagic acid content (52.4 mg/L and 86.4 mg/L), total phenolic content (TPC, 550.1 mg GAE/L) and radical scavenging activity (RSA, 4742.7 mmol TE/L). After the direct mixing of the extract and after encapsulation with starch as a carrier, the skincare emulsion and microemulsion were characterised by irritation potential (Zein test), transepidermal water loss (TEWL), red blood cell (RBC), and DPPH antioxidant test. The resulting preparations were of improved quality in comparison to the control hand cream, with a low skin irritation effect, lower TEWL, and higher antioxidant potential. This work complies with circular economy principles and green technology standards, and represents the efficient model on how to reuse natural resources through waste minimization.